Changes in Invasive Pneumococcal Disease Spectrum After 13-Valent Pneumococcal Conjugate Vaccine Implementation. (14th March 2019) - Levy, Corinne; Varon, Emmanuelle; Ouldali, Naim; Béchet, Stéphane; Bonacorsi, Stéphane; Cohen, Robert
Abstract: Background: Pneumococcal conjugate vaccine (PCV) implementation has led to a sharp decrease in invasive pneumococcal disease (IPD) due to the reduction in PCV serotypes. We aimed to describe the changes in the spectrum of IPD and its clinical presentations after 13-valent PCV (PCV13) implementation. Methods: This prospective, hospital-based, active surveillance involved 130 pediatric wards and microbiology departments throughout France. We analyzed IPD cases from 2011 to 2016 for which a pneumococcal isolate was sent to the National Reference Center for Pneumococci for serotyping. Clinical data recorded were medical history, vaccination status, type of IPD, clinical features, and short-term evolution. Results: Among 1082 IPD cases, we observed a 35.3% decrease (95% confidence interval, 29.2%–41.8%]) and the median age shifted from 38.3 months to 23.7 months ( P = .007). The change in IPD type was mostly due to a reduction in bacteremic pneumonia frequency (from 42.1% to 19.1%; P < .001). Among the emerging non-PCV13 types (NVTs), those known to have the highest disease potential (8, 12F, 24F, and 33F) were isolated more frequently in patients without underlying conditions and were able to induce all IPD clinical presentations including bacteremic pneumonia. Conversely, serotypes with lower disease potential (15A, 15BC, 16F, and 23B) were rarely isolated from bacteremic pneumonia cases and were particularly involved in IPD in patients with underlying conditions (35.8%). Conclusions: Besides the decrease in IPD after 7-valent, then 13-valent PCV implementation, the spectrum of the remaining IPD cases showed significant changes, with substantial discrepancies across NVTs implicated in terms of clinical features and underlying conditions. Abstract : A shift in the spectrum of invasive pneumococcal disease (IPD) occurred after 13-valent pneumococcal conjugate vaccine implementation, with a major reduction in bacteremic pneumonia. The nonvaccine types with the highest disease potential were isolated frequently from patients without underlying conditions and induced all IPD clinical presentations.